The Leadership Concept of Kyai in Pesantren: A Literature Analysis Based on Modern Educational Management Perspectives - Bustari, Bustari; Samad, Duski; Mamat, Firdaus ST. (ALSYS, 2025)
This study examines the leadership of kyai within the pesantren education system through a literature review grounded in modern educational leadership theories. While the role of the kyai has traditionally been analyzed from religious and normative standpoints, academic engagement with this leadership role through the lens of contemporary educational management remains limited. This article specifically explores the relevance of three modern leadership models, transformational leadership, servant leadership, and instructional leadership in understanding the multifaceted role of the kyai as both spiritual and educational leaders in pesantren. The findings indicate that the leadership characteristics of the kyai align closely with these models: as agents of change (transformational), as community servants (servant leadership), and as key drivers of educational quality (instructional leadership). This alignment suggests that integrating modern leadership theories can enhance the management and educational outcomes of pesantren without undermining their traditional values. The study concludes by recommending further empirical research to investigate the practical implementation of these leadership concepts in addressing contemporary challenges within Islamic boarding schools.